Combined effects of global DNA methylation, blood lead and total urinary arsenic levels on developmental delay in preschool children - Yuu-Hueih Hsu; Chih-Yin Wu; Hui-Ling Lee; Ru-Lan Hsieh; Ya-Li Huang; Horng-Sheng Shiue; Ying-Chin Lin; Mei-Chieh Chen; Yu-Mei Hsueh (Environmental Health)
Abstract DNA methylation is a critical step in brain development, 5-Methyl-2'-deoxycytidine (5mdC) is one of the global DNA methylation markers. Arsenic and lead exposures have been associated with neurotoxicity, which may be linked to epigenetic changes. Our research sought to investigate the correlation between 5mdC and developmental delay (DD) among preschoolers. Additionally, we assessed whether 5mdC modified the impacts of blood lead and total urinary arsenic levels on DD. We analyzed the concentrations of 5mdC, blood cadmium and lead, and total urinary arsenic in 174 children with DD and 88 healthy children. Global DNA methylation levels are expressed as the ratio 5mdC/2’-dexyguanosine (dG), called 5mdC (%). In our findings, elevated levels of blood lead and total urinary arsenic were significantly associated with DD risk among preschoolers. Furthermore, high 5mdC (%) was related with reduced risk of DD, with an odds ratio (OR) and 95% confidence interval (CI) of 0.14 (0.06 – 0.32). A notable multiplicative interaction was observed between low 5mdC (%) and elevated blood lead levels to increase OR of DD, with OR and 95% CI was 9.51 (4.18 – 21.64). The findings provide evidence of the combined effects of reduced 5mdC (%) and high blood lead concentrations, increasing the OR of DD.